High-speed kymography identifies the immediate effects of voiced vibration in healthy vocal folds - Pimenta, Regina Aparecida; Dájer, María Eugenia; Hachiya, Adriana; Cordeiro, Gislaine Ferro; Tsuji, Domingos Hiroshi; Montagnoli, Arlindo Neto (International Archives of Otorhinolaryngology, 2013)
Introduction: The effects of voiced vibration technique can be assessed by laryngeal imaging. Kymographic images derived from high-speed videoendoscopy allow actual visualization of vocal folds vibration.Purpose: The aim of this study is to identify the immediate effects of the voiced vibration technique in healthy vocal folds using high-speed digital laryngeal imaging.Methods: Samples were obtained from 15 healthy subjects with no history of voice disorders (6 men and 9 women aged 21 to 43 years). High-speed videoendoscopy recordings were performed before and after the voiced vibration technique. Kymographic images were obtained using high-speed videoendoscopy. The vocal folds were examined in their open and closed positions and the characteristics of the opening and closing phases were determined. A customize computational routine was used quantify these parameters. The closing, opening, and speed quotients were also calculated.Results: In this study, women displayed statistically significant differences in opened phase (P = 0.05*), closed phase (P = 0.046*), and closing phase (P = 0.026*) phase characteristics. Men displayed the highest difference rate in opening time characteristics (P = 0.06). The closing and opening quotients for the female group showed significant differences (P = 0.029* and P = 0.049*, respectively). The speed quotient exhibited statistically significant differences in the male group (P = 0.048*). Conclusion: The kymographic images indicated that the immediate effect of the voiced vibration technique was smooth contact in healthy vocal fold vibration.
Keywords: High-speed digital imaging; Kymography; Voiced vibration; Voice